Potential Markers of Neurocognitive Disorders After Cardiac Surgery: A Bibliometric and Visual Analysis - Ji, Linna; Li, Fang (Frontiers in Aging Neuroscience, 2022)
Background: Identifying useful markers is essential for diagnosis and prevention of perioperative neurocognitive disorders (PNDs). Here, we attempt to understand the research basis and status, potential hotspots and trends of predictive markers associated with PNDs after cardiac surgery via bibliometric analysis. Methods: A total of 4609 original research articles and reviews that cited 290 articles between 2001 and 2021 were obtained from the Web of Science Core Collection (WoSCC) as the data source. We used the software CiteSpace to generate and analyze visual networks of bibliographic information, including published years and journals, collaborating institutions, co-cited references, and co-occurring keywords. Results: The number of annual and cumulative publications from 2001 to 2021 has been increasing on the whole. The Harvard Medical School was a very prolific and important institution in this field. The journal of ANN THORAC SURG (IF 4.33) had the most publications, while NEW ENGL J MED was the most cited journal. Neuron-specific enolase (NSE), S100b and kynurenic acid were frequently discussed as possible markers of PNDs in many references. Cardiopulmonary bypass (CPB) was a keyword with high frequency (430) and sigma (6.26), and inflammation was the most recent burst keyword. Conclusion: The issue on pPotential markers of PNDs has received growing attention across various disciplines for many years. The research basis mainly focuses on three classic biomarkers of S100b, NSE and KYNA. The most active frontiers are the inflammation-related biomarkers (e.g. inflammatory cells, cytokines or mediators) and surgery-related monitoring parameters (e.g. perfusion, oxygen saturation and the depth of anesthesia).